2001
DOI: 10.1007/s004360100379
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic differentiation of Rodentolepis straminea (Goeze, 1752) and Rodentolepis microstoma (Dujardin, 1845) (Hymenolepididae)

Abstract: The two related species, Rodentolepis straminea (Goeze, 1782) and Rodentolepis microstoma (Dujardin, 1845) (Cestoda, Hymenolepididae), both parasites of rodents, were compared morphologically and electrophoretically. Adult worms were isolated from three wild rodent species of the family Muridae (Apodemus flavicollis, Apodemus sylvaticus, and Mus musculus) from three different sites in Spain and France. Although these two species were strikingly similar in morphological appearance, some of the morphological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 25 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…However, Casanova et al [15] suggested independent status for them. The results of Haukisalmi et al [13] fully supported the independent status of R. straminea and R. microstoma as host-specific parasites of Apodemus and Mus , respectively, and the present results based on the ITS1 sequences also confirm that they are independent species (data not shown) [GenBank: JN258054 for R. straminea ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Casanova et al [15] suggested independent status for them. The results of Haukisalmi et al [13] fully supported the independent status of R. straminea and R. microstoma as host-specific parasites of Apodemus and Mus , respectively, and the present results based on the ITS1 sequences also confirm that they are independent species (data not shown) [GenBank: JN258054 for R. straminea ].…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, it should be amended by the inclusion of cricetoid hook shape because the type species of the genus, R. straminea, possesses cricetoid rather than fraternoid, rostellar hooks (see [6][7][8]10,11,17,22,33,[40][41][42][43]). We consider the records of R. straminea with fraternoid rostellar hooks as misidentifications (e.g., [4,5]).…”
Section: Discussionmentioning
confidence: 99%
“…Species of Nomadolepis significantly differ from species of Rodentolepis (sensu stricto) and its type species R. straminea in several important morphological characters: rostellar hooks of fraternoid type (vs rostellar hooks of cricetoid type); ovary consisting of three lobes (vs fan-shaped); saccate bilobed uterus (vs labyrinthine uterus); uterus not extending beyond osmoregulatory canals (vs uterus extending laterally beyond osmoregulatory canals) [7,8,10,11,17,19,21]. However, due to the lack of a formal revision of Rodentolepis we provide here a [22][23][24] and testes situated in a triangle at an obtuse angle.…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1891, Blanchard [5] transferred the species to the genus Hymenolepis and provided an expanded description of the species. Although Bear and Tenora [6] suggested synonymy between H. microstoma and H. straminea (Goeze, 1782), species status of H. microstoma historically has been widely accepted, and molecular data have shown both species to represent independent, albeit closely related, lineages [7,8]. In contrast, the genus Hymenolepis has itself been overhauled on several occasions and its membership and internal structure remain controversial.…”
Section: Introductionmentioning
confidence: 99%